Hydrosol Scattering Matrix Inversion Across a Fresnel Boundary - Foster, Robert; Gray, Deric J.; Koestner, Daniel; El-Habashi, Ahmed; Bowles, Jeffrey (Frontiers in Remote Sensing, 2022)
We exhibit a proof-of-concept laboratory study for inversion of the partial Mueller scattering matrix of hydrosols from polarimetric observations across a smooth Fresnel boundary. The method is able to derive the 9 Mueller matrix elements relating to linear polarization for scattering angles between 70 and 110 degrees. Unlike prior studies of this nature, we utilize measurements from a hyper-angular polarimeter designed for passive remote sensing applications to derive the Mueller matrix, and tailor the polarimetric data reduction approach accordingly. We show agreement between the inversion results and theoretical Mueller matrices for Rayleigh scattering and Mie theory. The method is corroborated by measurements made with a commercial LISST-VSF instrument. Challenges and opportunities for use of the technique are discussed.